Experimental determination of Cd2+ adsorption mechanism on low-cost biological waste. - Ismail, Farhah Amalya; Aris, Ahmad Zaharin (Springer Verlag, 2013)
Carbonate shells have an astonishing ability in the removal of Cd2+ in a short time period with emphasis on being a low cost adsorbent. In the present study, the sorption capacity of carbonate shells was studied for Cd2+ in batch experiments. The influence of different carbonate shell sizes and physico-chemical factors were evaluated and the results were analyzed for its correlation matrices by using Predictive Analytics Software (PASW). The mineralogy state of aqueous solution regarding the saturation index was simulated using PHREEQC to identify the Cd2+ uptake mechanism. The Cd uptake rates were calculated as well as Ca2+, HCO 3 − concentration, pH, ambient humidity and temperature were measured. Cd2+ removal of 91.52% was achieved after 5 h adsorption. The adsorption efficiencies were significantly influenced by pH as they increased with the increase of pH from acidic solution (5.50±0.02) to slightly alkaline (7.60±0.05). In addition, the mineralogy state of aqueous solution calculated from PHREEQC confirmed that the increment of Ca2+ and HCO 3 − concentrations in solution was attributed to the dissolution of carbonate shells. Moreover, the ion exchange adsorption mechanism of Cd2+ toward Ca2+ was identified as the process involved in Cd2+ uptake.